The Influence of Family Support and Emotional Intelligence on Self-Acceptance in Kidney Failure Patients Undergoing Hemodialysis - Yanto, Novri (Newinera Publisher, 2025)
The low level of self-acceptance in hemodialysis patients with kidney failure indicates the complexity of internal factors (such as emotional intelligence) and external factors (such as family support) that may influence the psychological quality of life of patients. The purpose of this study is to experimentally determine how family support and emotional intelligence affect self-acceptance in kidney failure patients undergoing hemodialysis. Using multiple linear regression analysis, this study sampled 100 kidney failure hemodialysis patients. The findings of the study suggest that emotional intelligence and family support play a significant role in the self-acceptance of kidney failure hemodialysis patients. Kidney failure patients may feel better about themselves during hemodialysis sessions by improving their emotional abilities and receiving greater family support.